ECONOMIC FEDERALISM IN RUSSIA: CONSTITUTIONAL AND LEGAL ASPECTS - Nikita A. Sysoev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article characterizes the development of small and medium business in Russia after it gained sovereignty and adopted the Constitution of the Russian Federation on 12 December 1993. The author shows stages of developing free market relations and management of regional economy in Russia as a result of constitutional and legal reforms which started in early 1990-s and continue at present. Issues dealing with advantages of free market in comparison with planned economic relations were raised. The author highlighted issues of the federal structure of the Russian state. Economic federalism in Russia which has constitutional and legal guarantees is shown as a motivating factor for stable economic growth not only for certain regions but for the country in general.